2013
DOI: 10.1370/afm.1539
|View full text |Cite
|
Sign up to set email alerts
|

National Evidence on the Use of Shared Decision Making in Prostate-Specific Antigen Screening

Abstract: PURPOSE Recent clinical practice guidelines on prostate cancer screening using the prostate-specific antigen (PSA) test (PSA screening) have recommended that clinicians practice shared decision making-a process involving clinician-patient discussion of the pros, cons, and uncertainties of screening. We undertook a study to determine the prevalence of shared decision making in both PSA screening and nonscreening, as well as patient characteristics associated with shared decision making.METHODS A nationally repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
94
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 54 publications
8
94
1
1
Order By: Relevance
“…We defined shared decision making using a framework similar to that employed by Han and collegues, 8 which includes necessary components of shared decision making according to ACS and AUA recommendations. 3,4 These components include informing patients about the advantages and disadvantages of PSA testing, as well as uncertainties regarding the test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined shared decision making using a framework similar to that employed by Han and collegues, 8 which includes necessary components of shared decision making according to ACS and AUA recommendations. 3,4 These components include informing patients about the advantages and disadvantages of PSA testing, as well as uncertainties regarding the test.…”
Section: Methodsmentioning
confidence: 99%
“…2 Previous studies have shown that most men undergoing PSA testing reported either no discussion or only heard about the benefits of the test. 8,9 Other studies have shown variability and inadequacy of shared decision making. [9][10][11][12][13] It is not known, however, whether the use of shared decision making has changed in the wake of the shifting PSA-screening recommendations and practices at the national level.…”
Section: Introductionmentioning
confidence: 99%
“…37 US men describe not having engaged in shared decision making with their clinician when making decisions about Pca screening. 38 The decision to undergo Pca screening must involve an explicit discussion between patient and clinician of the possible benefits weighed against expected harms.…”
Section: Additional Guidelines/ Resourcesmentioning
confidence: 99%
“…7 They discovered that 88% of unscreened men and 39% of men undergoing annual or near-annual screening received no elements of shared decision making.…”
mentioning
confidence: 99%